Hybrid Learning Readiness: Techno Pedagogical Skills and Digital Competence Education - Ika Korika Swasti; Endang Sholihatin (Nusantara Science and Technology Proceedings, 2022)
This study aims to examine techno-pedagogical skills to realize digital competence in the hybrid learning process. This study used a case study method, collecting data through questionnaires and in-depth interviews (FGD) from informants and a sample of 35 people. The research location is at UPN "Veteran" Jawa Timur. The results showed that there were differences in techno-pedagogical skills between teachers based on age. Teachers aged <35 years have the speed to adapt to the use of information technology, electronic presentation skills, web-based course development tools (web-based course development tools), and knowledge of computer security that supports learning so that they have more skills in the use of information and communication technology for online lectures. The findings of this study are the basis for creating a knowledge-sharing development model to improve techno-pedagogical skills to achieve digital competence in hybrid learning.